PERILAKU REMAJA DALAM MENGKONSUMSI MINUMAN KERAS DI DESA HILINDRASORAYA KECAMATAN TOMA KABUPATEN NIAS SELATAN TAHUN 2021 - Totona Zanolo Dao; Fatolosa Hulu; Sesuaikan Sarumaha (Universitas Nias Raya, 2022)
The behavior of consuming liquor among teenagers in Hilindrasoraya Village, started from the habit of teenagers gathering to consume liquor to warm the body. The habit of teenagers often gathering together while consuming liquor, causes teenagers to be affected and join in consuming liquor. The purpose of this study was 1) to determine the behavior of adolescents in consuming liquor in Hilindrasoraya village, Toma district. 2) to find out the factors that cause adolescent behavior in consuming liquor in Hilindrasoraya village, Toma district. The method used in this research is descriptive qualitative method. Informants in this study are local village youth who consume liquor, local village officials and parents. From the results of the study, the behavior of teenagers in consuming liquor in Hilindrasoraya village is increasingly disturbing parents and even the community. This adolescent behavior can certainly be dangerous for the wearer because it can affect the mind, mood and behavior, and cause damage to the functions of the body's organs. The effect is to stimulate, calm, relieve pain, anesthetize, and make you happy. The factors that cause adolescent behavior in consuming liquor in Hilindrasoraya village are caused by friendship relations, the influence of the work environment, and the circulation of liquor in the community. The researcher's suggestions are 1) for teenagers in Hilindrasoraya Village, so they don't behave in a negative way and can damage a bright future. 2) for the community, it is more directed to teenagers to behave politely and do positive things for the progress and peace of Hilindrasoraya Village. 3) for parents, increasing attention and supervision of their teenage children and forbidding their children not to consume alcohol.